Running the rails : capital and labor in the Philadelphia Transit Industry - Wolfinger, James (Cornell University Press, 2016)
Philadelphia exploded in violence in 1910. The general strike that year was a notable point, but not a unique one, in a generations-long history of conflict between the workers and management at one of the nation’s largest privately owned transit systems. In Running the Rails, James Wolfinger uses the history of Philadelphia’s sprawling public transportation system to explore how labor relations shifted from the 1880s to the 1960s. As transit workers adapted to fast-paced technological innovation to keep the city’s people and commerce on the move, management sought to limit its employees’ rights. Raw violence, welfare capitalism, race-baiting, and smear campaigns against unions were among the strategies managers used to control the company’s labor force and enhance corporate profits, often at the expense of the workers’ and the city’s well-being.Public service workers and their unions come under frequent attack for being a "special interest" or a hindrance to the smooth functioning of society. This book offers readers a different, historically grounded way of thinking about the people who keep their cities running. Working in public transit is a difficult job now, as it was a century ago. The benefits and decent wages Philadelphia public transit workers secured - advances that were hard-won and well deserved - came as a result of fighting for decades against their exploitation. Given capital’s great power in American society and management's enduring quest to control its workforce, it is remarkable to see how much Philadelphia’s transit workers achieved.